Accuracy of Tools to Differentiate Single From Recurrent Fallers Pre-Frail Older Women - Gallo da Silva, Tamires Terezinha; Melo Filho, Jarbas; Biesek, Simone; Vojciechowski, Audrin Said; Borba, Victória Zeghbi Cochenski; Gomes, Anna Raquel Silveira (Frontiers in Public Health, 2022)
Objectives: To analyze and to compare musculoskeletal and functional performance; to present cutoff points to differentiate pre-frail community-dwelling older women regarding their fall history: non fallers (0 falls); fallers (single fall) and recurrent fallers (≥2 falls). Method: Cross-sectional, retrospective study, with 90 pre-frail community-dwelling older women (71.20±4.49 years), according to Fried criteria. We assessed the peak torque (PT) (Isokinetic Dynamometer); the muscle architecture/mass (Ultrasound/Dual-Energy X-Ray Absorptometry) and the following functional performance: usual gait speed (UGS); fast gait speed (FGS); walking speed reserve (WSR); cadence and step length; Timed Up and Go. Results: Recurrent fallers presented lower UGS (1.12±0.18m/s vs 1.29±0.28m/s; p=0.05); isometric PT of knee extensors in comparison to fallers (89.88±20.99Nm vs 115.55±23.09Nm; p=0.01); and FGS in comparison to fallers (1.35±0.26m/s vs 1.50±0.29m/s; p=0.03) and non-fallers (1.35±0.26m/s vs 1.52±0.26m/s; p=0.01). The outcomes that differentiated the fallers and non-fallers were both the WSRdiff (≤0.26m/s) and WSRratio (≤1.25m/s), while to differentiate recurrent fallers from non-fallers were FGS (≤1.44m/s) and the step length (≤73cm). And to differentiate recurrent fallers and fallers, UGS (≤1.12m/s); FGS (≤1.34m/s); step length (≤73cm); PT knee extension (≤114.2Nm); PT knee flexion (≤46.3Nm), and PT ankle dorsiflexion (≤22.1Nm). Conclusion: Recurrent fallers community-dwelling pre-frail older women presented a worse musculoskeletal and functional performance when compared to non-fallers and fallers. Gait speed, step length, PT of both knee extension and flexion, as well as ankle dorsiflexion can be used to identify both single and recurrent fallers pre-frail older women, contributing to guide interventions and to prevent falls and fractures.